PENDIDIKAN KEWIRAUSAHAAN DAN EKONOMI KREATIF DI DESA PASANGGRAHAN KECAMATAN PABUARAN KABUPATEN SERANG - Nikke Yusnita Mahardini; Neneng Sri Suprihatin; Kodriyah Kodriyah (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2021)
The implementation of “Pengabdian Kepada Masyarakat (PKM)” in Pasanggrahan Village is based on the constraints faced by the local village community in realizing the entrepreneurial spirit. Some of these obstacles include the lack of knowledge about entrepreneurship and creativity in creating product innovation. The purpose of carrying out PKM activities is to provide alternative solutions by conducting entrepreneurship education and training for local village communities. This activity is carried out through three stages, namely: (1) the preparatory stage: conducting observations and interviews, completing documents, and designing activities; (2) core stage: the implementation of entrepreneurship education seminars and training in making entrepreneurial products. PKM implementers provide training in making mustopa bananas by using bananas as the main ingredient which is the potential of Pabuaran Village; (3) final stage: the focus of activities on the evaluation of activities and preparation of the final report. All three stages have been implemented at 100%. The results obtained in the implementation of PKM are the increasing level of understanding of seminar participants and training on entrepreneurship in producing creative and innovative products through exploiting the potential of the village.